2021
DOI: 10.1101/2021.01.05.422575
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cholesteryl Hemiazelate Induces Lysosome Dysfunction and Exocytosis in Macrophages

Abstract: OBJECTIVEA key event in atherogenesis is the formation of lipid-loaded macrophages, lipidotic cells, which exhibit irreversible accumulation of undigested modified low-density lipoproteins in lysosomes. This event culminates with the loss of cell homeostasis, inflammation and cell death. In this study we propose to identify the chemical etiological factors and understanding the molecular and cellular mechanisms responsible for the impairment of lysosome function in macrophages.APPROACH AND RESULTSUsing shotgun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, an interactome study of injured lysosomes, revealed an interaction between Gal9, another galectin known to be recruited to damaged lysosomes, and VAMP7 68 , a SNARE protein involved in the membrane fusion of lysosomes with the plasma membrane. Nevertheless, how fusion machinery associated with secretory lysosomes, such as VAMP7 and CD63/LAMP3 [69][70][71][72] , is speci cally recruited to damaged lysosomes is still unclear. Interestingly, a very recent report showed increased cellular secretion in response to αsynuclein-induced lysosomal damage through a mechanism that relies on the autophagic secretory pathway, with a direct contribution of Gal3, Trim16 (tripartite motif containing 16) and ATG16L1 (autophagy related 16 like1) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, an interactome study of injured lysosomes, revealed an interaction between Gal9, another galectin known to be recruited to damaged lysosomes, and VAMP7 68 , a SNARE protein involved in the membrane fusion of lysosomes with the plasma membrane. Nevertheless, how fusion machinery associated with secretory lysosomes, such as VAMP7 and CD63/LAMP3 [69][70][71][72] , is speci cally recruited to damaged lysosomes is still unclear. Interestingly, a very recent report showed increased cellular secretion in response to αsynuclein-induced lysosomal damage through a mechanism that relies on the autophagic secretory pathway, with a direct contribution of Gal3, Trim16 (tripartite motif containing 16) and ATG16L1 (autophagy related 16 like1) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Lysosome positioning within cells was measured as previously described 70 . Brie y, cell membrane and nuclear contours were extracted manually using ImageJ selection tools.…”
Section: Image Analysismentioning
confidence: 99%
“…These modifications significantly affect the physicochemical and biological properties of the lipoproteins (Aviram, 1993;Hoff and Hoppe, 1995). One of the major chemical modifications of LDL is oxidation, involving free radical mediated lipid peroxidation, which was already demonstrated to occur in vivo (Gibson et al, 2018;Domingues et al, 2021). The presence of different subsets of lipases and oxygenases in the arterial wall may result in the occurrence of numerous forms of modified LDL in vivo.…”
Section: Ldl Oxidationmentioning
confidence: 99%
“…The pro-atherogenic potential of oxLDL has been solidly established (Goldstein et al, 1979;Steinberg et al, 1989;Jerome and Lewis, 1990;Aviram, 1993), although the role of each particular bioactive molecule remains largely unexplored. While most research has focused on the atherogenicity of oxidized phospholipids and oxysterols, our recent studies suggest that the end products of CE oxidation, cholesteryl hemiesters, may be responsible for some of the proatherogenic properties ascribed to oxLDL (Estronca et al, 2012;Domingues et al, 2017Domingues et al, , 2021.…”
Section: Ldl Oxidationmentioning
confidence: 99%